Interactive effects of ethanol on ulcerative colitis and its associated testicular dysfunction in pubertal BALB/c mice (2017)
Available epidemiological reports have indicated an increase in the incidence of ulcerative colitis, as well as alcohol consumption, globally. The present study investigated the possible interactive effects of ethanol consumption on ulcerative colitis and its associated testicular dysfunction using six groups of 12 pubertal mice each. Group I (Control) mice received drinking water alone. Group II mice received ethanol alone at 5 g/kg body weight. Group III mice received 2.5% dextran sulphate sodium (DSS) in drinking water followed by normal drinking water. Groups IV, V, and VI mice received DSS followed by ethanol at 1.25, 2.5, and 5 g/kg, respectively. Administration of ethanol to mice with ulcerative colitis intensified the disease-activity index with marked reduction in colon length, colon mass index, body weight gain, and organo-somatic indices of testes and epididymis when compared with the DSS-alone group. Moreover, ethanol exacerbated colitis-mediated decrease in enzymatic and non-enzymatic antioxidants but increased the oxidative stress and inflammatory biomarkers in the testes and epididymis. The diminution in luteinizing hormone, follicle stimulating hormone, and testosterone levels was intensified following administration of ethanol to mice with ulcerative colitis that were administered 5 g/kg ethanol alone. The decrease in sperm functional parameters and testicular spermatogenic indices as well as histopathological damage in colon, testes, and epididymis was aggravated following administration of ethanol to mice with ulcerative colitis. In conclusion, the exacerbating effects of ethanol on ulcerative colitis-induced testicular dysfunction are related to increased oxidative stress and inflammation in the treated mice.